THE ESTABLISHMENT OF A GUESTHOUSE ON A RESIDENTIAL PROPERTY: COMPLYING WITH RESTRICTIVE CONDITIONS OF TITLE AND TOWN PLANNING SCHEME PROVISIONS - Henk Delport (Obiter, 2022)
Guesthouses and bed and breakfast establishments (B&Bs) have grown tremendously in popularity throughout South Africa. Most of them are situated in residential areas and are part of, or linked to, an existing dwelling on a property. They are normally operated by the home owner, who usually (but not always) resides on the property. Travellers are attracted by competitive rates, personal service and an informal atmosphere in homely surroundings away from the hustle and bustle of the inner city. The home owner, in turn, is attracted by the income generating potential of the venture and the relative ease with which the operation can be conducted on site from home. The quality and nature of the establishments vary from the very basic to ultra luxurious, some offering facilities and accommodation comparable to (perhaps even exceeding) the best offered by some top hotels. In fact many guesthouses come close to being boutique hotels, having extensive guest facilities and a variety of accommodation options, such as luxurious suites and self-catering apartments. Guesthouses and B&Bs also differ in size and get-up, many comprising no more than one or two of the existing bedrooms in a house. Others have five or more bedrooms specifically built and designed by an owner for the purposes of operating a guesthouse on his property. In the latter instance the bedrooms often do not adjoin the existing dwelling on the property, but constitute a free-standing building on the property. Another variation is where an entire house is converted into a guesthouse, with the owner residing in a flatlet on the property. Most guesthouses, like B&Bs, provide breakfast while many also cater for supper.Given the increasing demand for guesthouse accommodation on the part of both tourists and business travellers, it is not surprising that many property owners are keenly contemplating embarking on a guesthouse venture. Obviously many aspects need to be considered, including the legal issues. This note focuses on the legal requirements from a property law perspective. This is not merely of academic interest. In the recent case of Van Rensburg v Nelson Mandela Metropolitan Municipality (unreported, case no 1668/06 SECLD) the High Court ordered a property owner in an upmarket residential suburb of Port Elizabeth to demolish a second storey tothe garage on the property, as well as another free-standing building, both of which had been erected for the purposes of conducting a guesthouse business on the property. The demolition application was brought by a neighbouring owner who complained, inter alia, that the extensions to the garage and the erection of the free-standing building were carried out contrary to certain restrictive conditions contained in the title deed of the property, namely that (i) the property may be used for residential purposes only; (ii) only one single house dwelling for use by a single dwelling family and ordinary outbuildings required for such use may be built on the property; and (iii) no garage other than for ordinary use for persons residing on the erf may be erected on the property. Non-compliance with the relevant legal requirements can therefore have far-reaching consequences for the would-be guesthouse owner.